MELEDAKKAN IESQ (INTELEKTUAL, EMOSIONAL DAN SPIRITUAL QUOTIENT) UNTUK MERAIH SUKSES DALAM BERWIRAUSAHA - Maslichan, Maslichan (potensio, 2013)
Entrepreneurship will have a positive impact on the burden of the government to create jobs will be reduced. Even we who opened jobs for other people. God will be very dear to us because our minds goodness rjeki gave the hook to his servants. In development we can see that the entrepreneurial world can reduce the number of unemployed and will indirectly increase the state income tax through. By looking at these things with an increase in the number of entrepreneurs it is not impossible that Indonesia can get rid of the crisis that is now being twisted economy. In entrepreneurship we must sharpen our brains, our hearts soften and brighten our spiritual or we often call IESQ. The purpose of this paper is to understand how to improve the success IESQ entrepreneurship.Â Keywords: Intellectual Quotient, Emotional Quotient, Spiritual Quotient and Entrepreneurial